Hubungan Pengetahuan Teori dan Kemampuan Praktik Pemesinan Terhadap Kesiapan Praktik Kerja Industri Siswa SMK - Dedik Hariyanto; Eddy Sutadji; Suharmanto Suharmanto (Jurnal Dinamika Vokasional Teknik Mesin, 2016)
The objectives of this study are (1) to determine the correlation between the knowledge of machining theory and the readiness for industrial work practice; (2) to determine the correlation between the ability of machining practice and the readiness for industrial work practice; and (3) to determine the correlation between the knowledge of machining theory and the ability of machining practice to the readiness of industrial work practice. This study can be categorized as correlation study with a quantitative approach. The population of the study is the XI graders of Machining Department in SMK PGRI Wlingi Blitar on the academic year of 2014/2015. Data were collected using questionnaire and documentation. Data analysis techniques being using were descriptive analysis, simple linear regression and two predictors multiple regressions. According to the data analysis, it can be concluded that: (1) there is a significant positive correlation between the knowledge of machining theory and the readiness for industral practice, (2) there is a significant positive correlation between the ability of machining practice and the readiness for industry practice, and (3) there is a significant positive correlation between the knowledge of machining theory and the ability of machining practice to the readiness for industrial practice. The coefficient of determination (Adjusted R Square) is 0,831 (83,1%).----------------------------------------------------------------------------------Tujuan penelitian ini adalah untuk mengetahui hubungan antara: (1) pengetahuan Teori Pemesinan terhadap kesiapan Praktik Kerja Industri, (2) kemampuan Praktik Pemesinan terhadap kesiapan Praktik Kerja Industri, dan (3) pengetahuan Teori Pemesinan dan kemampuan Praktik Pemesinan terhadap kesiapan Praktik Kerja Industri. Penelitian ini termasuk penelitian deskriptif dengan pendekatan kuantitatif. Populasi dari penelitian ini adalah siswa kelas XI Program Keahlian Teknik Pemesinan SMK PGRI Wlingi Kabupaten Blitar Tahun Ajaran 2014/2015. Teknik Pengumpulan data menggunakan kuesioner dan dokumentasi. Teknik analisis data menggunakan analisis deskriptif, analisis regresi linier sederhana, dan analisis regresi ganda dua prediktor. Hasil penelitian menunjukkan bahwa: (1) terdapat hubungan positif yang signifikan antara pengetahuan Teori Teknik Pemesinan terhadap kesiapan Praktik Kerja Industri. (2) terdapat hubungan positif yang signifikan antara kemampuan Praktik Teknik Pemesinan terhadap kesiapan Praktik Kerja Industri Industri. (3) terdapat hubungan positif yang signifikan antara pengetahuan Teori Teknik Pemesinan dan kemampuan Praktik Teknik Pemesinan terhadap kesiapan Praktik Kerja Industri. Koefisien determinasi (Adjusted R Square) adalah sebesar 0,831 (83,1%).